Conciliation: labour dispute - Ali Mohamed, Ashgar Ali; Tan, Yeak Hui (CLJ Publication, 2020)
As workers have been constantly shopping for better working conditions, disputes are inevitable and thus, cannot be totally eliminated. However, handling these disputes in the best possible manner is absolutely necessary. Speedy disposal of disputes would ensure inter alia, a steady relationship between the workmen and their employers. Such constructive means of amicable resolution will result in sustainable industrial peace. Most industrialised countries, including many developing nations, have established a specialist labour court to resolve their workplace disputes. In Malaysia, labour disputes are referred and adjudicated in the Industrial Court7 and the Labour Court.8 In light of the above, this chapter discusses on the use of conciliation as a means of resolving labour disputes with particular reference to claims involving dismissal without just cause or excuse under the Industrial Relations Act 1967 (‘IRA’).